Otimização e validação de método de extração do herbicida florpirauxifen-benzil em amostras de água - Luis Henrique Silva Vieira (2022)
The herbicides are great allies in the constant search for greater world agricultural productivity. Given the scenario of many years of indiscriminate and erroneous use of herbicides, weeds ended up creating resistance to several of the compounds present in the market. The florpyrauxifen benzyl is a systemic herbicide, of the auxin mimetic class, used in weeds in rice cultivation areas in flooded or rainfed systems. The National Health Surveillance Agency (ANVISA) authorized the commercialization of this pesticide, however it did not establish instructions with a method of extraction and quantification of residues of this compound as a form of environmental monitoring. Therefore, the present study aimed to optimize and validate the liquidliquid extraction with low temperature purification (LLELTP) to determine the florpyrauxifenbenzyl content in water samples by high performance liquid chromatography with array detection of diodes (HPLCDAD) and evaluate the stability of the compound in groundwater. In the chromatographic analysis, the parameters of temperature, column type, wavelength, composition and flow of the mobile phase were evaluated in a univariate way. The LLELTP was optimized through a full factorial experiment (23), having as factors: extractor phase (8.0 mL of acetonitrile and 6.5 mL of acetonitrile +1.5 mL of ethyl acetate), ionic strength (0.0 and 0.1 g of NaCl) and freezing time (60 and 120 min). In the experiments performed, the recovery ranged from 95.84 to 105.4% with a relative standard deviation of less than 1.5. The LLELTP was selective, precise, exact, linear in the range of 4.00 to 150 µg L1, and the limit of quantification was 4.00 µg L1. The stability study of the compound in water revealed its degradation in 25 days and DT50 in approximately 5 days. It was possible to optimize and validate the LLELTP method coupled to HPLCDAD, being an easy and efficient method that can be used in the monitoring of florpyrauxifenbenzyl in water samples.